Analysis of Factors Influencing the Decision of the Elderly in Choosing a Place of Residence - Rahmah, Eka Maulana; Hikmawati, Isna (Proceedings Series on Health & Medical Sciences, 2025)
Elderly individuals are defined as those who have reached the age of 60 years and above. According to the March 2022 Susenas data, 10.48 percent of the population consists of elderly individuals. One of the main challenges faced by the elderly is making decisions regarding their place of residence. The data shows that 7.10% of elderly individuals live alone, 22.07% live only with their spouse, and 33.66% live with their nuclear family. This study uses a quantitative approach with a cross sectional approach. Data collection was carried out in June 2024 using an instrument, namely a questionnaire sheet distributed directly. The sampling technique is purpose sampling with a sample of 93 elderly respondents aged >60 years, able to communicate well verbally and in writing, willing to be respondents. The variables measured were economic conditions, health conditions, social welfare and the availability of health facilities which were analyzed with data analyzed by the chi-square test. The results indicate that poor economic conditions (82.8%), health status assessed by MMSE and the KATZ index as healthy (100%), and blood pressure measurements as healthy (88.2%) are factors influencing the decision. High social support (84.9%), availability of supporting health care facilities (87.1%), and choosing to live with a spouse or family (92.5%) were also significant. There is a significant relationship between economic conditions (p= 0.0001, OR [95% CI] = 1.778 [1.154-1.239]) and social support (p= 0.0001, OR [95% CI] = 0.500 [0.296-0.884]) with the choice of residence. No significant correlation was found between health status (p= 0.690, OR [95% CI] = 1.093 [1.023-1.168]) and the availability of health care facilities (p= 1.000, OR [95% CI] = 0.880 [0.097-8.018]) with the choice of residence. Economic conditions and social support are significantly related to the choice of residence. Family support and attention to the elderly can improve their well-being.